DEVELOPMENT OF WOMEN ENTREPRENEURS AND IDENTIFYING THE FACTORS THAT FORCE THEM TO STAY DIGITALLY (CAHIERS MAGELLANES-NS, 2024)
Women entrepreneurs join the money movement to get financially involved and work on their social standing. These entrepreneurs have had a significant impact on all areas of business, despite the crumbling circumstances and the lack of accessibility of various drives and means to drive and promote women's entrepreneurship in emerging markets, women are still more insecure than men to start and run their organizations and bring less money with slower business development a. The motives are a lack of tutoring access, opportunities to improve their innate skills, and a sense of helplessness and extremism. Women are still economically dependent on men. The young women work to encounter their financial needs, which is possible thanks to their work knowledge and openness to education and urbanization. This has contributed to the development of female business visionaries. Therefore, in this time of social change and development, it is crucial to examine women's businesses in this computerized climate, what open doors have empowered them to pursue a business venture and how they tend to energize and engage in striving effectively. In the current study, 240 samples were selected from Kerala randomly; the sample only includes women entrepreneurs who opt for digital marketing in their ventures. The study finds that adopting digital marketing in small sectors helps raise the satisfaction level of women entrepreneurs. This study also attempts to find the key variables that influence women entrepreneurs to step forward into the digital marketing world.